Analysis of Dynamic Recrystallization of Ice from EBSD Orientation Mapping - Montagnat, Maurine; Chauve, Thomas; Barou, Fabrice; Tommasi, Andrea; Beausir, Benoît; Fressengeas, Claude (Frontiers in Earth Science, 2015)
We present high resolution observations of microstructure and texture evolution during dynamic recrystallization (DRX) of ice polycrystals deformed in the laboratory at high temperature (≈0.98Tm). Ice possesses a significant viscoplastic anisotropy that induces strong strain heterogeneities, which result in an early occurrence of DRX mechanisms. It is therefore a model material to explore these mechanisms. High resolution c-axis measurements at sample scale by optical techniques and full crystallographic orientation measurements by cryo- Electron Back Scattering Diffraction (EBSD) provide a solid database for analyzing the relative impact of the macroscopic imposed stress versus the local and internal stress field on DRX mechanisms. Analysis of misorientation gradients in the EBSD data highlights a heterogeneous dislocation distribution, which is quantified by the Nye tensor estimation. Joint analyses of the dislocation density maps and microstructural observations highlight spatial correlation between high dislocation density sites and the onset of nucleation taking place by grain-boundary bulging, subgrain rotation or by the formation of kink-bands.